Direct Substitution of a Hydroxyl Group by a Carboxyl Group at the Benzylic Position in Benzyl Alcohols by Electrochemical Reduction in the Presence of Carbon Dioxide: Improvement Enabling Electrochemical Direct Carboxylation of Benzyl Alcohols even in the Absence of an Electron-withdrawing Group on the Phenyl Ring - Mizuki HAYAMA; Hisanori SENBOKU (Electrochemistry, 2023)
Electrochemical carboxylation of benzyl alcohols even in the absence of an electron-withdrawing group on the phenyl ring was successfully carried out by improving our previous electrolysis conditions. Constant current electrolysis of benzyl alcohols including diphenylmethanol in DMSO containing 0.1 mol dm−3 Bu4NBF4 in the presence of carbon dioxide using an undivided cell equipped with a platinum plate cathode and a magnesium rod anode at room temperature resulted in direct substitution of a hydroxyl group by a carboxyl group at the benzylic position to give the corresponding arylacetic acids including diphenylacetic acid in moderate to good yields. Although the effect of DMSO as a solvent is still unclear, the results indicate the potential for a useful, convenient, and eco-friendly synthetic method for arylacetic acids from benzyl alcohols.